Influence of weak layer heterogeneity and slab properties on slab tensile failure propensity and avalanche release area - Gaume, J.; Chambon, Guillaume; Eckert, Nicolas; Naaim, Mohamed; Schweizer, J. (The Cryosphere, 2015)
[Departement_IRSTEA]Eaux [TR1_IRSTEA]RIVAGE International audience Dry-snow slab avalanches are generally causedby a sequence of fracture processes, including failure initiation in a weak snow layer underlying a cohesive slab followed by crack propagation within the weak layer (WL) andtensile fracture through the slab. During past decades, theoretical and experimental work has gradually increased ourknowledge of the fracture process in snow. However, our limited understanding of crack propagation and fracture arrestpropensity prevents the evaluation of avalanche release sizesand thus impedes hazard assessment. To address this issue,slab tensile failure propensity is examined using a mechanically based statistical model of the slab-WL system based onthe finite element method. This model accounts for WL heterogeneity, stress redistribution by slab elasticity and possi-ble tensile failure of the slab. Two types of avalanche releaseare distinguished in the simulations: (1) full-slope release ifthe heterogeneity is not sufficient to stop crack propagationand trigger a tensile failure within the slab; (2) partial-sloperelease if fracture arrest and slab tensile failure occur dueto the WL heterogeneity. The probability of these two release types is presented as a function of the characteristics ofWL heterogeneity and the slab. One of the main outcomes isthat, for realistic values of the parameters, the tensile failurepropensity is mainly influenced by slab properties. Hard andthick snow slabs are more prone to wide-scale crack propagation and thus lead to larger avalanches (full-slope release).In this case, the avalanche size is mainly influenced by topographical and morphological features such as rocks, trees,slope curvature and the spatial variability of the snow depthas often claimed in the literature.